Beyond Drug Use: Inclusion of Psychological Well-Being as an Outcome in Evaluation of Treatments for Substance Abuse Disorder - Farhana Sabri; Mohd Khairul Anuar Rahimi; Abd Halim Mohd Hussin (Perkhidmatan Awam Malaysia, 2024)
Non-Indexed Publication